Systematic literature review on sterile injectable dates of use, stability and implications for use - Dewi, I Gst A A Gangga Samala; Putri, Lucienne Agatha Larasati Nugraha; Silalahi, Lydia Devy; Dewi, I Gusti Ayu Widha Paramistya; Hapsari, Meivanti Diva; Dewa, Julio Angga Purnama; Sarayawati, Kadek Ayu Mas; Prasetya, I Wayan Sindhu Wahyu; Dewi, Ni Pande Kadek Sinta; Noviyanti, Ni Putu Rika; Sari , Putri Ayu Puspita; Rajeswari, Ni Kadek Ida; Wahyuni, Ni Luh Komang; Wulandari, Dewi; Warditiani, Ni Kadek (PT. Mega Science Indonesia, 2025)
Beyond-use date (BUD) is crucial for the stability of injectable preparations. However, there is a knowledge gap and a lack of information regarding BUD determination in injection preparations. Therefore, a systematic review is needed to address the BUD of injection preparations. This study aimed to provide comprehensive insights into the stability, BUD data, and associated implications for injectable preparations through a systematic literature review approach. This study employed a systematic literature review guided by the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA). The inclusion criteria were research articles from national and international journals discussing the BUD of sterile injection preparations published in the last 10 years. Fourteen of the 19 articles related to BUD were selected for analysis. The analysis revealed that the stability of the 19 sterile injection preparations was significantly influenced by the characteristics of the preparation, storage conditions, and type of drug. These factors substantially affect the effectiveness and safety of drugs. Intravenous sterile injections involve several critical steps to ensure the safety and efficacy of the medications used. Adhering to BUD guidelines for intravenous injections is crucial for maintaining drug quality, which can help prevent infections or adverse reactions in patients. The stability of sterile injection preparations, which is influenced by various factors, has direct implications for BUD determination. This review highlights the importance of considering these factors when determining BUD to ensure patient safety.